Phasin PhaP1 is involved in polyhydroxybutyrate granules morphology and in controlling early biopolymer accumulation in Azospirillum brasilense Sp7 - María de los Angeles Martínez-Martínez; Bertha González-Pedrajo; Georges Dreyfus; Lucía Soto-Urzúa; Luis Javier Martínez-Morales (AMB Express, 2019)
Abstract Phasins are amphiphilic proteins involved in the regulation of the number and size of polyhydroxybutyrate (PHB) granules. The plant growth promoting bacterium Azospirillum brasilense Sp7 accumulates high quantities of bioplastic PHB as carbon and energy source. By analyzing the genome, we identified six genes that code for proteins with a Phasin_2 domain. To understand the role of A. brasilense Sp7 PhaP1 (PhaP1Abs) on PHB synthesis, the phaP1 gene (AMK58_RS17065) was deleted. The morphology of the PHB granules was analyzed by transmission electron microscopy (TEM) and the PHB produced was quantified under three different C:N ratios in cultures subjected to null or low-oxygen transfer. The results showed that PhaP1Abs is involved in PHB granules morphology and in controlling early biopolymer accumulation. Using RT-PCR it was found that phasin genes, except phaP4, are transcribed in accordance with the C:N ratio used for the growth of A. brasilense. phaP1, phaP2 and phaP3 genes were able to respond to the growth conditions tested. This study reports the first analysis of a phasin protein in A. brasilense Sp7.